A Novel Hybrid Microdosimeter for Radiation Field Characterization Based on the Tissue Equivalent Proportional Counter Detector and Low Gain Avalanche Detectors Tracker: A Feasibility Study - Missiaggia, M.; Pierobon, E.; Castelluzzo, M.; Perinelli, A.; Cordoni, F.; Centis Vignali, M.; Borghi, G.; Bellinzona, E. V.; Scifoni, E.; Tommasino, F.; Monaco, V.; Ricci, L.; et al. (Frontiers in Physics, 2021)
In microdosimetry, lineal energies y are calculated from energy depositions ε inside the microdosimeter divided by the mean chord length, whose value is based on geometrical assumptions on both the detector and the radiation field. This work presents an innovative two-stages hybrid detector (HDM: hybrid detector for microdosimetry) composed by a Tissue Equivalent Proportional Counter (TEPC) and a silicon tracker made of 4 Low Gain Avalanche Diode (LGAD). This design provides a direct measurement of energy deposition in tissue as well as particles tracking with a submillimeter lateral spatial resolution. The data collected by the detector allow to obtain the real track length traversed by each particle in the TEPC and thus estimates microdosimetry spectra without the mean chord length approximation. Using Geant4 toolkit, we investigated HDM performances in terms of detection and tracking efficiencies when placed in water and exposed to protons and carbon ions in the therapeutic energy range. The results indicate that the mean chord length approximation underestimate particles with short track, which often are characterized by a high energy deposition and thus can be biologically relevant. Tracking efficiency depends on the LGAD configurations: 34 strips sensors have a higher detection efficiency but lower spatial resolution than 71 strips sensors. Further studies will be performed both with Geant4 and experimentally to optimize the detector design on the bases of the radiation field of interest. The main purpose of HDM is to improve the assessment of the radiation biological effectiveness via microdosimetric measurements, exploiting a new definition of the lineal energy (y_T), defined as the energy deposition ε inside the microdosimeter divided by the real track length of the particle.